2013
DOI: 10.1007/s12020-013-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of pharmacological therapy in Cushing’s disease

Abstract: Cushing's disease (CD) is a severe endocrine condition caused by an adrenocorticotropin (ACTH)-producing pituitary adenoma that chronically stimulates adrenocortical cortisol production and with potentially serious complications if not or inadequately treated. Active CD may produce a fourfold increase in mortality and is associated with significant morbidities. Moreover, excess mortality risk may persist even after CD treatment. Although predictors of risk in treated CD are not fully understood, the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 167 publications
0
13
0
8
Order By: Relevance
“…3; Rocheville et al 2000, Ren et al 2003, de Bruin et al 2009). Studies on different tumor models, including pituitary adenomas, revealed a higher potency of BIM-23A779, BIM-23A760, and BIM-23A781 (chimeric molecules containing both SST and dopamine structural elements) in controlling tumor cell growth (Ferone et al 2013). Further studies of patients with CD are required.…”
Section: Chimeric Compoundsmentioning
confidence: 99%
See 4 more Smart Citations
“…3; Rocheville et al 2000, Ren et al 2003, de Bruin et al 2009). Studies on different tumor models, including pituitary adenomas, revealed a higher potency of BIM-23A779, BIM-23A760, and BIM-23A781 (chimeric molecules containing both SST and dopamine structural elements) in controlling tumor cell growth (Ferone et al 2013). Further studies of patients with CD are required.…”
Section: Chimeric Compoundsmentioning
confidence: 99%
“…It is highly expressed in Potential novel therapeutic targets for CD. From left to right; the effect of V3 receptor-specific antagonists that could lead to a new class of agents that can suppress ACTH secretion in corticotrope adenomas (Ferone et al 2013). After blocking of EGFR, a tyrosine kinase receptor, POMC expression is attenuated, and inhibition of corticotrope cell proliferation and apoptosis can be induced (Fukuoka et al 2011).…”
Section: Peroxisome Proliferator-activated Receptor Gamma Ligandsmentioning
confidence: 99%
See 3 more Smart Citations